Anaesthesia recommendations for Camp(t)omelic dysplasia - Albermann, Matthias; Prottengeier, Johannes (Anästhesiologie & Intensivmedizin, 2020)
Disease summary: Camp(t)omelic dysplasia (CD) is an autosomal dominantly inherited disorder of the SOX9 gene (17p24.3-q25.1), caused by de novo mutation or defective chromosomal recombination [1,2,3]. The SOX9 gene encodes a transcription factor that affects chondrogenesis, testicular development and determines phenotypic sex characteristics [4,5]. Pathological findings can be grouped in osseous and non-osseous disorders. Osseous features are the naming bowed femora and tibia (campomel = bent limb; camptomel bowed limb), short stature, vertebral abnormalities with cervical instability and possible cord compression (paraplegia), only eleven rib pairs, facial dysmorphia (Pierre Robin sequence, short neck), cleft palate, progressive scoliosis, club feet and dislocatable hips. Non-osseous features include laryngotracheobronchomalacia with respiratory compromise, ambiguous genitalia with sex reversal (female external genitalia with 46 XY karyotype), congenital heart disease (ventricular septal defect, VSD), hypotonia, kidney malformation (hydronephrosis) and neurological disorders including hydrocephalus and hearing impairment [6,7]. No clinical feature is obligatory. When femora and tibia are not affected, it is termed as acamp(t)omelic camp(t)omelic dysplasia (ACD). The estimated prevalence ranges from 1:10,000 to <1:1,000,000 [8,9]. Because of the rare occurrence of CD, an exact prevalence is uncertain. Currently, only symptomatic therapy is available. Most affected patients die in the neonatal period due to respiratory insufficiency [10]. Operative treatment is performed if individuals reach infancy.
CRIS-Team Scopus Importer:2020-03-31
Keywords: Camp(t)omelic dwarfism; Camp(t)omelic syndrome

The prehospital intravenous access assessment: a prospective study on intravenous access failure and access delay in prehospital emergency medicine - Prottengeier, Johannes; Albermann, Matthias; Heinrich, Stefan; Birkholz, Torsten; Gall, Christine; Schmidt, Joachim (European Journal of Emergency Medicine, 2016)
Intravenous access in prehospital emergency care allows for early administration of medication and extended measures such as anaesthesia. Cannulation may, however, be difficult, and failure and resulting delay in treatment and transport may have negative effects on the patient. Therefore, our study aims to perform a concise assessment of the difficulties of prehospital venous cannulation.We analysed 23 candidate predictor variables on peripheral venous cannulations in terms of cannulation failure and exceedance of a 2 min time threshold. Multivariate logistic regression models were fitted for variables of predictive value (P<0.25) and evaluated by the area under the curve (AUC>0.6) of their respective receiver operating characteristic curve.A total of 762 intravenous cannulations were enroled. In all, 22% of punctures failed on the first attempt and 13% of punctures exceeded 2 min. Model selection yielded a three-factor model (vein visibility without tourniquet, vein palpability with tourniquet and insufficient ambient lighting) of fair accuracy for the prediction of puncture failure (AUC=0.76) and a structurally congruent model of four factors (failure model factors plus vein visibility with tourniquet) for the exceedance of the 2 min threshold (AUC=0.80).Our study offers a simple assessment to identify cases of difficult intravenous access in prehospital emergency care. Of the numerous factors subjectively perceived as possibly exerting influences on cannulation, only the universal - not exclusive to emergency care - factors of lighting, vein visibility and palpability proved to be valid predictors of cannulation failure and exceedance of a 2 min threshold.
EVALuna2:5542

Using Arden Syntax for the generation of intelligent intensive care discharge letters - Kraus, Stefan; Castellanos, Ixchel; Albermann, Matthias; Schüttler, Christina; Prokosch, Hans-Ulrich; Staudigel, Martin; Toddenroth, Dennis (Exploring complexity in health: an interdisciplinary systems approach; proceedings of MIE 2016 at HEC2016, 2016)
UnivIS-Import:2017-12-18:Pub.2016.tech.IMMD.infome.usinga

Using Arden Syntax for the Generation of Intelligent Intensive Care Discharge Letters - Kraus, Stefan; Castellanos, Ixchel; Albermann, Matthias; Schüttler, Christina; Prokosch, Hans-Ulrich; Staudigel, Martin; Toddenroth, Dennis (Studies in health technology and informatics, 2016)
Discharge letters are an important means of communication between physicians and nurses from intensive care units and their colleagues from normal wards. The patient data management system (PDMS) used at our local intensive care units provides an export tool to create discharge letters by inserting data items from electronic medical records into predefined templates. Local intensivists criticized the limitations of this tool regarding the identification and the further processing of clinically relevant data items for a flexible creation of discharge letters. As our PDMS supports Arden Syntax, and the demanded functionalities are well within the scope of this standard, we set out to investigate the suitability of Arden Syntax for the generation of discharge letters. To provide an easy-to-understand facility for integrating data items into document templates, we created an Arden Syntax interface function which replaces the names of previously defined variables with their content in a way that permits arbitrary custom formatting by clinical users. Our approach facilitates the creation of flexible text sections by conditional statements, as well as the integration of arbitrary HTML code and dynamically generated graphs. The resulting prototype enables clinical users to apply the full set of Arden Syntax language constructs to identify and process relevant data items in a way that far exceeds the capabilities of the PDMS export tool. The generation of discharge letters is an uncommon area of application for Arden Syntax, considerably differing from its original purpose. However, we found our prototype well suited for this task and plan to evaluate it in clinical production after the next major release change of our PDMS.
EVALuna2:164